Preliminary Study on Feasibility of Manufacturing Injection-molded Composite Using Cellulosic Materials - Ji Hyun Tak; Min Seo Kim; Ji Young Lee (BioResources)
Wastepaper-derived fibers, natural starch binders, and micro-fibrillated cellulose (MFC) additives were preliminarily studied as key components in injection-moldable bio-composite formulations. Commercially available paper cups coated with polyethylene, corn starch, and MFC prepared in a laboratory were selected as raw materials. Since the injection molding machine is yet to be developed, handsheets were prepared as a substitute for the future injection-molded composites, and their physical properties were evaluated to assess the promising formulation candidates of recycled fibers, binder, and reinforcing agent. The optimal paper cup powder–starch ratio was 60:40, which balanced the tensile strength, elongation at break, and burst strength of the material while maintaining good processing characteristics and avoiding problems related to dewatering and adhesion to equipment during drying. The incorporation of up to 5% (by weight) MFC considerably improved the mechanical properties of the sheets by enhancing their fiber–fiber bonding. However, increasing the MFC content above 5% prolonged the dewatering time, compromising process efficiency, and making handsheet preparation impossible. These findings suggested that used paper cups, when combined with starch and MFC, could be effectively recycled into injection-molded composite materials, thereby contributing to environmental conservation and the advancement of resource circulation in manufacturing.